Effect of Vitamin C to Malondialdehyde (MDA) Level in Medical Students Jember University with Psychological Stress - Rahmad Adi Prasetyo; Laksmi Indreswari; Aris Prasetyo (Journal of Agromedicine and Medical Sciences, 2018)
Medical students may to receive excessive psychological stressors during their education. The response of stress experienced by the body can activate the sympathetic neuron pathways and complex system hypothalamic pituitary-adrenal (HPA) axis. This can lead to a state of oxidative stress in the body through an increase of metabolism, mitochondrial oxidation, neutrophil activity, glycolysis and lipolysis processes. The level of malondialdehyde (MDA) is the most frequently used parameter for assessing oxidative stress conditions in the body. Vitamin C is an antioxidant that can neutralize the effects of free radicals through electron transfer mechanisms. This study aims to determine the effect of vitamin C on MDA levels in medical students of Jember University who experienced psychological stress. This is clinical test study with Quasi Experimental approach that used Pretest - Posttest Control Group Design with 32 sample of medical students Jember University who experienced psychological stress. The level of psychological stress was determined through questionnaire of Depression Anxiety Stress Scale (DASS) version Damanic Indonesian while the examination of MDA levels by the TBARs test. The result of T test analysis between MDA level at pretest and posttest is p= 0,000. It shows that there is effect of vitamin C consumption to the malondialdehyde (MDA) level in medical students Jember University with psychological stress. Keywords: Psychological stress, Malondialdehyde, Vitamin C